Russian Federation : Financial Sector Assessment Program: Technical Note-Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for the Russian Federation in the areas of anti-money laundering and combating the financing of terrorism. Some authorities have gained a better understanding of money laundering and terrorism financing risks. Swift finalization of the national risk assessment will further advance that understanding and the use of a risk-based approach by all concerned agencies and reporting entities. Preventive measures related to politically exposed persons and reporting of suspicious transactions were updated and are largely in line with the Financial Action Task Force standards. However, the definition of politically exposed persons must be further amended, and the effectiveness of the measures should be enhanced.